2016
DOI: 10.1542/peds.2015-2467
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Intergenerational Cycle of Disadvantage: The Three Generation Approach

Abstract: Health disparities in the United States related to socioeconomic status are persistent and pervasive. This review highlights how social disadvantage, particularly low socioeconomic status and the health burden it brings, is passed from 1 generation to the next. First, we review current frameworks for understanding the intergenerational transmission of health disparities and provide 4 illustrative examples relevant to child health, development, and well-being. Second, the leading strategy to break the cycle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 85 publications
2
85
1
Order By: Relevance
“…Poverty exhibits direct and indirect effects on families' social, emotional, and physical health and well-being, disproportionately affecting the capacity to address basic needs and access healthcare and education as well as overall morbidity and mortality (Evans & Kim, 2013;Johnson, Riis, & Noble, 2016). The burden of income inequality, coupled with the chronic stress associated with resource-poor environments (Cheng et al, 2016), leads to increased challenges related to parenting for families living in poverty as compared to their higher income counterparts (Brooks-Gunn & Duncan, 1997;Jocson & McLoyd, 2015;Pascoe et al, 2016). Just as low-income populations are denied access to buffering supports, parents living in poverty may lack access to those resources which specifically support positive parenting, such as the ability to spend time with their children, procurement of childcare and transportation, and access to parenting information and social support (Johnson, Riis, & Noble, 2016;Kaiser & Delaney, 1996).…”
Section: Impact Of Poverty On Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty exhibits direct and indirect effects on families' social, emotional, and physical health and well-being, disproportionately affecting the capacity to address basic needs and access healthcare and education as well as overall morbidity and mortality (Evans & Kim, 2013;Johnson, Riis, & Noble, 2016). The burden of income inequality, coupled with the chronic stress associated with resource-poor environments (Cheng et al, 2016), leads to increased challenges related to parenting for families living in poverty as compared to their higher income counterparts (Brooks-Gunn & Duncan, 1997;Jocson & McLoyd, 2015;Pascoe et al, 2016). Just as low-income populations are denied access to buffering supports, parents living in poverty may lack access to those resources which specifically support positive parenting, such as the ability to spend time with their children, procurement of childcare and transportation, and access to parenting information and social support (Johnson, Riis, & Noble, 2016;Kaiser & Delaney, 1996).…”
Section: Impact Of Poverty On Parentingmentioning
confidence: 99%
“…Many negative outcomes are associated with poverty during childhood, including increased risk of chronic disease and stress as well as behavior and emotional problems, difficulties in concentration and memory, and delays in language development (American Psychological Association, 2013;Bitsko et al, 2016;Duncan, Ziol-Guest, & Kalil, 2010;Luby et al, 2013;Pascoe, Wood, Duffee, & Kuo, 2016). Studies also have demonstrated that children living in poverty during early childhood experience negative effects into adulthood (Cheng, Johnson, & Goodman, 2016;Duncan et al, 2010).…”
mentioning
confidence: 99%
“…Income Inequality [10,] is a measure of relative poverty, known to be associated with poorer child health outcomes [11][12][13][14][15][16][17] and is the other major socio-economic context in which all health services operate.…”
Section: Socio-economic Contextmentioning
confidence: 99%
“…On the other hand, these 21 Western countries are amongst the very richest in the world [8], though this is not to deny there are differences between them. For example based upon US Census Bureau data, who report mortality by ethnicity, African American children die at virtually double the rate of White 0-4 year olds and such feature occurs in other Western countries but here we are reviewing the nation's mortality rates in their entirety [6,9,[11][12][13][14][15][16][17].…”
Section: Clinical Outputsmentioning
confidence: 99%
“…It is here that intergenerational transmission of health disparities arises. It is of concern, as a child born to poor parents is likely to remain poor as an adult and, if he or she becomes a parent, to raise poor children …”
Section: Introductionmentioning
confidence: 99%